Oxidative Stress in Takotsubo Syndrome—Is It Essential for an Acute Attack? Indirect Evidences Support Multisite Impact Including the Calcium Overload—Energy Failure Hypothesis - Manousek, Jan; Kala, Petr; Lokaj, Petr; Ondrus, Tomas; Helanova, Katerina; Miklikova, Marie; Brazdil, Vojtech; Tomandlova, Marie; Parenica, Jiri; Pavkova Goldbergova, Monika; Hlasensky, Jiri (Frontiers in Cardiovascular Medicine, 2021)
Indirect evidences in reviews and case reports on Takotsubo syndrome (TTS) support the fact that the existence of oxidative stress (OS) might be its common feature in the pre-acute stage. The sources of OS are exogenous (environmental factors including pharmacological and toxic influences) and endogenous, the combination of both may be present, and they are being discussed in detail. OS is associated with several pathological conditions representing TTS comorbidities and triggers. The dominant source of OS electrones are mitochondria. Our analysis of drug therapy related to acute TTS shows many interactions, e.g., cytostatics and glucocorticoids with mitochondrial cytochrome P450 and other enzymes important for OS. One of the most frequently discussed mechanisms in TTS is the effect of catecholamines on myocardium. Yet, their metabolic influence is neglected. OS is associated with the oxidation of catecholamines leading to the synthesis of their oxidized forms – aminochromes. Under pathological conditions, this pathway may dominate. There are evidences of interference between OS, catecholamine/aminochrome effects, their metabolism and antioxidant protection. The OS offensive may cause fast depletion of antioxidant protection including the homocystein-methionine system, whose activity decreases with age. The alteration of effector subcellular structures (mitochondria, sarco/endoplasmic reticulum) and subsequent changes in cellular energetics and calcium turnover may also occur and lead to the disruption of cellular function, including neurons and cardiomyocytes. On the organ level (nervous system and heart), neurocardiogenic stunning may occur. The effects of OS correspond to the effect of high doses of catecholamines in the experiment. Intensive OS might represent “conditio sine qua non” for this acute clinical condition. TTS might be significantly more complex pathology than currently perceived so far.